Peningkatan Aktivitas dan Hasil Belajar Mata Pelajaran IPS dengan Metode Student Team Achievement Division (STAD) - Airtanto (Universitas Pancasakti Tegal, 2018)
Learning Social science (IPS) especially on atmospheric matter and hidrosfer found not yet optimal learning process, Students consider less interesting, boring and less perceived meaning by student in everyday life so that student attitude in IPS lesson very low. Teachers only explain the material contained in textbooks without regard to student activity and creativity, thus causing the students' learning ability to be inhibited. The aim of this action research was to improve student activity and achivement of social science subject by implementing cooperative learning model of Student Team Achievement Division (STAD) Type. Participant of the research was students of class VIIB SMP Negeri 2 Warureja, Tegal regency at second semester academic year 2016/2017. The result revealed that the implementation of cooperative learning model of Students Team Achivement Division (STAD) could improve students social science achivement. The improvement was 11 % from 72%at the first cycle to 83% at the second cycle. The improvement of achivement was 3% from 72% at the first cycle to 75% at the second cycle.